2005
DOI: 10.1158/1078-0432.ccr-04-2685
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a R115777-Resistant Human Multiple Myeloma Cell Line with Cross-Resistance to PS-341

Abstract: The farnesyl transferase inhibitor R115777 has been found to have clinical activity in diverse hematopoietic tumors. Clinicalefficacy, however, doesnot correlate with Rasmutationstatus orinhibition of farnesyl transferase. To further elucidate the mechanisms by which R115777 induces apoptosis and to investigate drug resistance, we have identified and characterized a R115777-resistant human myeloma cell line. 8226/R5 cells were found to be at least 50 times more resistant to R115777 compared with the parent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
(25 reference statements)
1
29
0
Order By: Relevance
“…Culture supernatants were centrifuged (200 Â g for 10 minutes), and stored at À80 C as conditioned media. (27); MM.1R cells are resistant to dexamethasone (28). The cell lines were cultured in RPMI-1640 medium supplemented with 10% fetal calf serum (both from Euroclone, Milan, Italy).…”
Section: Patients and Cell Isolationmentioning
confidence: 99%
“…Culture supernatants were centrifuged (200 Â g for 10 minutes), and stored at À80 C as conditioned media. (27); MM.1R cells are resistant to dexamethasone (28). The cell lines were cultured in RPMI-1640 medium supplemented with 10% fetal calf serum (both from Euroclone, Milan, Italy).…”
Section: Patients and Cell Isolationmentioning
confidence: 99%
“…Buzzeo et al have also demonstrated that G2/M arrest induced by bortezomib's proteasome inhibition is not correlated with the sensitivity of cells to bortezomib-induced apoptosis. 36 We showed that bortezomib efficiently inhibits proteasome activity in all tested leukemia cells, as demonstrated by proteasome activity analysis and by efficient NF-kB inhibition even in bortezomib-resistant leukemia cells ( Figure 1C and D). However, bortezomib induces differential apoptotic effects in these leukemia cells.…”
Section: Discussionmentioning
confidence: 51%
“…First, we generated a resistant cell Page 11 of 31 A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 resistance to this drug [27] and also greater than the resistance of SUDHL-4 lymphoma cells (Fig. 6), previously used in several works as a model of bortezomib resistance [28][29][30].…”
Section: Apo2l/trail Induces Apoptosis In Bortezomib-resistant Cell Lmentioning
confidence: 99%